CENSORSHIP IN SOCIAL NETWORKS AS A SOCIAL PRACTICE IN THE CONTEXT OF GLOBAL TRANSFORMATIONS - КИРИЛ ДЗІГОРА (Cхід, 2021)
The article clarifies the socio-philosophical nature of censorship, the methods of its action and the restrictions it may impose on the information presented on social networks. Using specific examples from the work of social networks, the author argues that censorship creates the availability of information. The problem of user's subjectivity in the virtual space have been described. The complexity and contradiction of the phenomenon of censorship on the Internet have been disclosed. Technical, non-technical and indirect methods of implementing censorship frameworks for information in cyberspace have been analyzed. The technical methods are described in more detail in the article. They were grouped according to the following classification: methods that slow down the operation of services; methods that block the activity of services; methods that block information with human participation; methods that block information using algorithms; marking information as unreliable It is stated that censorship today complicates access to information instead of completely blocking it. The problem of new type of censorship on the Internet created by the recommendation systems have been considered. It is noted that the use of these systems enhances the subjectivity of users, and leads to the creation of echo cameras. Thus, the research hypothesis stating that “availability of information generates censorship” was confirmed with the above arguments and examples from the work of social networks.